Analisis Strategi Komunikasi Pemasaran Terpadu Museum Batik Kota Pekalongan dalam Meningkatkan Pengunjung - M. Wisnu Darmawan; Trimanah (Indo Publishing, 2025)
This study analyzes the Integrated Marketing Communications Strategy of the Pekalongan City Batik Museum in Increasing Visitors. The research method used is qualitative research. The subject of this study is the Pekalongan Batik Museum, while the object of this study is the integrated marketing communications strategy. Overall, the communication actions undertaken by the Pekalongan Batik Museum in conveying IMC messages are the result of collecting and assembling various strategic inputs, ranging from digital data, audience profiles, internal input, social sensitivity, and public feedback. This process reflects the principles of Action Assembly Theory, where communication actions are not merely spontaneous but are the result of the compilation of contextual and organized information.